1987
DOI: 10.1002/dc.2840030208
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration biopsy of abdominal and retroperitoneal tumors in infants and children

Abstract: Fine-needle aspiration biopsy has been employed to establish morphologic diagnoses in abdominal and retroperitoneal tumors in 54 infants and children. A 0.4-0.7-mm gauge needle was used; the puncture was performed through the anterior abdominal wall in the abdominal tumors and by the lateral approach in the retroperitoneal tumors. Malignant tumors were discovered in 51 cases (94.4%). The nature of the lesion was recognized in 96.2%, and correct cell typing was achieved in 90.2%. The most frequent lesion was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Glomeruluslike structures were present in two cases in this study. Similar structures have been reported by Valkov et al 36 in one of their three cases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Glomeruluslike structures were present in two cases in this study. Similar structures have been reported by Valkov et al 36 in one of their three cases.…”
Section: Discussionsupporting
confidence: 91%
“…12,23,31,36 In the present study, the frequency of SRCT was also very high among intrathoracic and intraabdominal childhood malignancies (78.1%). This was significantly higher compared to the frequency of these tumors (13.2%) among adult malignancies (P < .001).…”
Section: Discussionmentioning
confidence: 76%
“…35,36 These therapeutic advances have encouraged the development and utilization of minimally invasive diagnostic test techniques for pediatric patients. 37,38 Multiple cytomorphologic descriptions for the major SRCN of childhood have been reported in the literature, but fewer reports have demonstrated the diagnostic utility of these features in separating the various small round cell malignancies of childhood. 6,[9][10][11]17,[22][23][24]31 The success of advanced chemotherapeutic protocols is based on definitive cell typing in order to select the most appropriate and specific combination of chemotherapeutic agents possible.…”
Section: Discussionmentioning
confidence: 99%
“…13,16,22,24,25,31,32,37,38 Akhtar et al 13 reported that individual cells with long cytoplasmic processes, fibrillary tangles, and pseudorosettes were characteristic of neuroblastoma. 13,16,22,24,25,31,32,37,38 Akhtar et al 13 reported that individual cells with long cytoplasmic processes, fibrillary tangles, and pseudorosettes were characteristic of neuroblastoma.…”
Section: Logistic Regression Analysis Of Srcnmentioning
confidence: 99%
“…The FNAC features of neuroblastic tumors have been amply described either as exclusive studies [9][10][11] or as a part of studies on pediatric malignancies or small round cell tumors. [12][13][14][15] The frequency of rosettes in FNA smears of neuroblastomas varies from 18.8% to 71.9%, with an average of 45.9% 9,10,13,15,16 Rosettes or rosettelike structures can be observed in nephroblastoma 15 and Ewing's sarcoma in rare cases. 17 Filamentous or fibrillary background material is also an important morphologic feature of neuroblastoma, observed in < 50-100% of cases, 9,10,13,15,16 but has not been observed in other small round cell tumors that are considered in the differential diagnosis of neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%